PERBEDAAN TINGKAT SELF DIRECTED LEARNING READINESS PADA MAHASISWA TAHUN PERTAMA, KEDUA DANKETIGA DI FAKULTAS KEDOKTERAN UNIVERSITAS MALAHAYATI - Abdul Halim Subiakto S; Sri Maria Puji Lestari (Jurnal Ilmu Kedokteran dan Kesehatan, 2019)
The higher level an ability of Self Directed Learning Readiness (SDLR) a student is directly proportional to the level of his performance, as a research of Chakravarthi shows the difference of score SDLR based a semester being undertaken by the subject, where is have an increased score of SDLR in every semester , Showed how longer students take the level of education than make it better the ability of SDLR's level.Objective in this research to determine whether there are differences of SDLR's level in the first year students, second and third in the Faculty of Medicine, Malahayati University. this study used quantitative research with cross sectional approach, the data is primary data, taken using a questionnaire on 444 students of medical school (148 students of the first year, 148 students of the second year, and 148 students of the third-year ) were conducted entirely in January till February 2016.The obtained, there is no comparison of SDLR's level in a first-year student and the third with a p-value is 0.012 (≤ 0.05),  interpretation of the results that there are different levels of SDLR is significant in the first-year students and third year, there was no difference in the first-year students and second year with a p-value 0.094 and also on the second year students and third year students with a p-value 0.358 which both have a p-value ≥ 0.05. There are differences in the level of SDLR in the first-year students and the third year at the Faculty of Medicine, Malahayati University